Characterization of polymorphic markers of endothelial dysfunction genes in secondary nephropathies in children with rheumatic diseases - Guzel K. Karymova; Igor V. Zorin (Лечащий Врач)
Background. The problem of diagnosing secondary kidney lesions associated with rheumatic diseases in children is given special attention in pediatrics. At the same time, early detection of renal lesions in children with rheumatic diseases is still difficult.Objective. The purpose of the study: the search for criteria for the early diagnosis of secondary nephropathies in children with RH remains relevant at the present stage. The role of identified candidate genes whose mutations are responsible for the development of secondary nephropathies in children is widely discussed in modern literature. It is relevant to assess the relationship of potential associations of mutations and allelic polymorphism of genes with clinical and paraclinical variants of kidney pathology in children with rheumatic diseases. The study of genetic factors of nephropathy formation in children with rheumatic diseases is necessary to identify a group of patients at high risk for the development of secondary nephropathies. The identification of genetic factors in the formation of nephropathy in children with rheumatic diseases will increase the effectiveness of the diagnosis of kidney pathology, since the carriage of significant genes or polymorphic alleles affects the formation and course of the disease, which has high theoretical and practical significance.Materials and methods. The article presents data from a study of polymorphism of folate cycle genes – methylenetetrahydrofolate reductase (MTHFR) A1298C, C677T, methionine synthase (MTR) A2756G, methionine synthase reductase (MTRR) A66G, endothelin-1 (EDN1 G7244T, EDN1 G7000A rs1800629) and tumor necrosis factor-α (TNF-α G4682A) y 124 patients with rheumatic diseases.Results. It has been proven that an increase in the frequency of the homozygous CC genotype of the MTHFR A1298C gene, the homozygous GG genotype of the MTRR A66G gene, the homozygous GG genotype of the MTR A2756G gene in children with secondary nephropathies in nodular connective tissue diseases are non-modifiable risk factors and additional criteria for diagnosing secondary kidney damage in children with nodular connective tissue diseases.